Impact of Digitalization on Sustainable Marketing of Commercial Properties in Benin City - Oyakhire, M. M.; Alao, D. O.; Seghosime, K. (International Journal of Real Estate, 2026)
Digitalization has revolutionized marketing practices in the commercial real estate sector worldwide, and Benin City, Nigeria, is no exception. This paper explores the impact of digitalization on sustainable marketing of commercial properties in Benin City, specifically focusing on how digital tools, such as social media platforms, online property listing portals, virtual tour applications, and mobile communication systems, have transformed marketing efficiency, lowered costs, and broadened market reach. The study also assesses the sustainability aspects of digital marketing in real estate, which include environmental, economic, and social outcomes. Utilizing a descriptive research design and relying on secondary sources, including peer-reviewed academic literature and professional reports from the Estate Surveyors and Valuers Registration Board of Nigeria (ESVARBON), the study concludes that digitalization has markedly enhanced property visibility and transaction speed while diminishing reliance on traditional marketing methods. Nonetheless, challenges such as insufficient power infrastructure, poor internet connectivity, limited digital skills among practitioners, and the prevalence of online fraud hinder the complete realization of these advantages. The paper advocates for improved digital capacity development for real estate professionals, increased investment in broadband infrastructure, and stringent regulatory oversight of online property advertising platforms.